2022
DOI: 10.46799/jss.v3i5.414
|View full text |Cite
|
Sign up to set email alerts
|

Key Success in The Transformation from Volume-Based to Value-Based Healthcare: A Scoping Review

Abstract: The medical cost trend had been increasing faster than the global inflation rate. Higher costs posed a significant problem for healthcare providers, payers, and eventually patients. The concept of value-based healthcare (VBHC), which emphasized the importance of measuring outcomes relative to the costs, was introduced to mitigate the impact of these medical trends. This research used a scoping review methodology to describe the factors that affect the shift from the conventional volume-based healthcare to valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, evaluating value solely based on costs is insufficient. According to a scoping review by Gunawan et al (2022) , most implementations of VBHC focus only on outcomes and costs, neglecting its multidimensional nature. None of the studies reported complete success in applying all aspects of VBHC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, evaluating value solely based on costs is insufficient. According to a scoping review by Gunawan et al (2022) , most implementations of VBHC focus only on outcomes and costs, neglecting its multidimensional nature. None of the studies reported complete success in applying all aspects of VBHC.…”
Section: Introductionmentioning
confidence: 99%
“…None of the studies reported complete success in applying all aspects of VBHC. Therefore, hospital leaders need to understand that VBHC adoption involves more than just partial implementation ( Gunawan et al, 2022 ). While traditional discussions of VBHC have emphasized its economic aspects, as noted by Kim et al (2013) and Kaplan and Porter (2011) , recent literature suggests the need to explore its psychosocial dimensions ( van Engen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the VBHC model emphasizes patientcentered approaches by placing the patients at the center of the healthcare process, involving them in shared decision-making, and prioritizing their preferences, values, needs, and outcomes (Hillary et al, 2016). These positive attributes of VBHC have led many healthcare organizations to start a transformation journey toward VBHC delivery systems, with "value" measurement being the first and foremost step in this transformation (Gunawan et al, 2022).…”
Section: List Of Tables and Figuresmentioning
confidence: 99%